(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract: Food allergies and nutritional intolerances are critical concerns for the hospitality industry, impacting guest safety and satisfaction. This research paper examines effective hotel management practices for addressing these dietary challenges. Key strategies include comprehensive staff training, clear communication channels, detailed menu information, cross-contamination prevention, customized meal preparation, and robust emergency procedures. Staff training ensures that personnel can recognize and respond to allergic reactions, while clear communication helps capture and address guest dietary needs accurately. Detailed menu information, including allergen labeling and allergen-free options, aids guests in making safe food choices. Preventing cross-contamination through dedicated utensils and strict hygiene practices is essential for minimizing risk. Customized meal preparation allows hotels to cater to specific dietary requirements, and established emergency procedures ensure a prompt response to allergic reactions. Collaboration with suppliers ensures ingredient safety, and guest feedback drives continuous improvement in allergen management practices. By implementing these comprehensive measures, hotels can provide a safer dining environment, enhance guest satisfaction, and build a positive reputation for accommodating diverse dietary needs. This paper offers a detailed examination of these practices and provides actionable recommendations for hotels to better manage food allergies and nutritional intolerances.